Given differential equation is "y'+ \\frac{1-3x^2}{x(1-x^2)}y=\\frac{1}{1-x^2} (\\clubs)" , clearly, it's a first order first and degree
differential equation of the form "y'+P(x)y=Q(x)" ,Thus integrating factor "(I.F)" is given by,
Hence, In this case I.F will be,
Now, let's calculate the integral first as follows
"\\int \\frac{1-3x^2}{x(1-x^2)}dx \\hspace{1cm} (\\star \\star)"Suppose, "f(x)=x(1-x^2)" ,clearly "f'(x)=1-3x^3" ,thus above integral has the form
"\\int \\frac{f'(x)}{f(x)}dx"And we already know that "\\int \\frac{f'(x)}{f(x)}dx=ln(f(x)) +constant"
Hence, "(\\star \\star)" will be "ln(x(1-x^2))" ,thus from "(\\star)"
"I.F=e^{ln(x(1-x^2)} =x(1-x^2)""\\big(\\because \\: e^{ln(f(x))}=f(x)\\big)" ,Now on multiply I.F in equation "(\\clubs)" we get,
where "c" is a constant. Hence, we are done.
Comments
Leave a comment